BILIARY REFLUX AFTER STANDARD LAPAROSCOPIC MINI-GASTRIC BYPASS IN PATIENTS WITH MORBID OBESITY: clinical consequences and functional-economic outcomes - Matkuliev, U.I.; Abduganiyev, J.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Introduction. While laparoscopic mini-gastric bypass (LMGB) is widely recognized for its simplicity and effectiveness in weight reduction, the incidence of postoperative biliary reflux remains a significant concern. This study evaluates the frequency, clinical manifestations, and organizational-economic impact of biliary reflux in patients undergoing standard LMGB, stratified by the presence or absence of gastroesophageal reflux disease (GERD) prior to surgery. Materials and Methods. A retrospective cohort analysis was conducted in 68 patients with morbid obesity who underwent standard LMGB. Patients were divided into two subgroups: with pre-existing GERD (n=32) and without GERD (n=36). Clinical symptoms, endoscopic findings, need for antireflux therapy, length of hospital stay, and resource expenditures were analyzed within 30 days postoperatively. Results. Biliary reflux symptoms were observed in 68.8% of GERD-positive and 13.9% of GERD-negative patients, with a significant difference in the incidence of postoperative regurgitation, heartburn, and nighttime epigastric discomfort (p<0.01). The frequency of “de novo” reflux in GERD-negative patients reached 28% by day 30. Endoscopic detection of bile in the gastric pouch was reported in 90.6% of GERD-positive cases. Patients with reflux had longer hospital stays (10.2±2.6 vs. 7.4±1.8 days), more frequent readmissions, and required symptom-relieving medications more than twice as often. Resource expenditures exceeded the base therapeutic cost by 63% in the GERD-positive subgroup. Conclusion. Standard LMGB without antireflux modification is associated with a high risk of biliary reflux, particularly in patients with pre-existing GERD. This complication significantly affects early clinical recovery and increases healthcare resource utilization. The findings support the need for anatomical or technical modification of the gastrojejunal configuration to prevent retrograde bile flow.